Design, simulation and fabrication of silicone rubber colonoscope tip for medical application. (25th April 2022) - Singh, Puneet Kumar; Srivastava, Pankaj Kumar; Krishna, Chimata Murali
Colonoscopy is a major tool to detect colon abnormality and colon cancer in the initial stage. Bio-inspired robots inspired by inchworm and elephant trunks are widely used in the medical field as colonoscopes. The colonoscope tip in this research work is made of silicone rubber which is hyper-elastic in nature in order to achieve distal end flexibility and comfort for patients. ABAQUS 2020 software is used for designing colonoscope tip. After inputting the necessary data, the developed colonoscope tip is simulated by applying pneumatic pressure in three holes provided at 120° apart. A central hole is also provided for the camera, biopsy tools etc. After that, the designed colonoscope tip is manufactured, and experiments are conducted using an experimental setup. The pneumatic air from the compressor is applied to a fabricated silicone colonoscope tip via hoses with pressure regulator and pressure sensor mounted on them, and displacement of the tip is measured. The experimental results obtained are quite close with the simulated results, and thus, the simulated results are validated.